Effects of intraperitoneal injection of microencapsulated Sertoli cells on chronic and presymptomatic dystrophic mice - Chiappalupi, Sara (Data Brief, 2015)
We report data about the effects of intraperitoneal (i.p.) injection of specific pathogen-free (SPF) porcine Sertoli cells (SeC) encapsulated into clinical grade alginate-based microcapsules (SeC-MC) on muscles of chronic and presymptomatic dystrophic, mdx mice. Mdx mouse is the best characterized animal model of Duchenne muscular dystrophy (DMD), an X-linked lethal myopathy due to mutation in the gene of dystrophin, which is crucial for myofiber integrity during muscle contraction. Our data show that three weeks after i.p. injection of SeC-MC significantly reduced adipose and fibrous tissue deposition, reduced macrophage infiltrate, and reduced numbers of damaged myofibers are found in muscles of 12-month-old mdx mice, which reproduce chronic DMD conditions. Compared with muscles of mock-treated mdx mice muscles of SeC-MC-treated mice show upregulation of the dystrophin paralogue, utrophin which is localized to the periphery of myofibers. Moreover, our data show that i.p. injection of SeC-MC into presymptomatic, 2-week-old mdx mice, although not fully preventing myofiber degeneration, results in protection against myofiber necrosis and muscle inflammation. Extensive discussion of these data can be found in Ref. [1].